COMPARATIVE ANALYSIS OF MODERN TIME SERIES FORECASTING METHODS FOR SOLVING PRACTICAL PROBLEMS - Сумець, Світлана; Удовенко, Сергій; Шергін, Вадим; Чала, Лариса (SWorldJournal, 2026)
The goal of this work is to develop a modified technology for error detection in text documents using a multilayer perceptron neural network. Each of the considered forecasting models has its own advantages and limitations when using them for the selected